On the Convergence of Labour Rights and Human Rights - Adams, Roy J. (Relations industrielles / Industrial Relations, 2001)
This article discusses Unfair Advantage: Workers' Freedom of Association in the United States under International Human Rights Standards and Your Voice at Work: Global Report under the Follow-up to the ILO Declaration on Fundamental Principles and Rights at Work. During the past decade a strong international consensus has emerged that holds that a set of core labor rights should be regarded as fundamental human rights. The appearance of these 2 reports indicates that the situation is rapidly changing.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employees; Freedom of Association; Globalization; HUMAN rights; Labor Unions; Labor relations; Research; Rights; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z